2008
DOI: 10.1016/j.cell.2008.04.030
|View full text |Cite
|
Sign up to set email alerts
|

XPD Helicase Structures and Activities: Insights into the Cancer and Aging Phenotypes from XPD Mutations

Abstract: Mutations in XPD helicase, required for nucleotide excision repair (NER) as part of the transcription/repair complex TFIIH, cause three distinct phenotypes: cancer-prone xeroderma pigmentosum (XP), or aging disorders Cockayne syndrome (CS), and trichothiodystrophy (TTD). To clarify molecular differences underlying these diseases, we determined crystal structures of the XPD catalytic core from Sulfolobus acidocaldarius and measured mutant enzyme activities. Substrate-binding grooves separate adjacent Rad51/RecA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
422
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(442 citation statements)
references
References 38 publications
14
422
2
4
Order By: Relevance
“…15,21 Our XP and TTD patients had XPD mutations that are similar to those previously published. 1,5,[8][9][10][11] All of our XP and TTD patients were compound heterozygotes for two different XPD mutations. Many XP patients had the common p.R683W mutation combined with other mutations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…15,21 Our XP and TTD patients had XPD mutations that are similar to those previously published. 1,5,[8][9][10][11] All of our XP and TTD patients were compound heterozygotes for two different XPD mutations. Many XP patients had the common p.R683W mutation combined with other mutations.…”
Section: Discussionmentioning
confidence: 87%
“…There are several reasons why we believe that the prediction by Moslehi et al 19 that mutations in the C-terminal region of XPD [8][9][10] cause pre-eclampsia may not be correct. There is a complex genotype-phenotype relationship between the location of mutations in the human XPD gene and the presence or absence of clinical features of XP or TTD.…”
Section: Moslehi Et Almentioning
confidence: 94%
See 1 more Smart Citation
“…The DNA helicase Rad3 (XPD in humans) is one of the ten subunits of the RNA polymerase transcription factor IIH and is vital for nucleotide excision DNA repair 33 . A prokaryotic homolog of Rad3 has been shown by biochemical and structural studies to contain an essential [4Fe-4S] cluster inserted into its helicase fold 31,34 . This protocol describes various experimental approaches to verify that these proteins in fact contain Fe/S clusters in the living cell.…”
Section: Introductionmentioning
confidence: 99%
“…R112H maps to a residue in contact with the 4Fe-4S cluster and disrupts the helicase activity of XPD. 42 Three of the four TTD cases in our study, which were not associated with preeclampsia were R112H homozygotes. These observations suggested that gestational complications in the R112H:T482D heterozygote TTD case were driven by the T482D allele.…”
Section: Discussionmentioning
confidence: 51%